2009
DOI: 10.1515/epoly.2009.9.1.48
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polymerization temperature on structure and properties of polyaniline

Abstract: Abstract:The influence of polymerization temperature (from -25 to +25 o C) on molecular weight, crystallinity, electrical conductivity, thermal and morphological properties of polyaniline has been investigated. Aniline was oxidized in an aqueous medium with ammonium persulfate and 1.0 M hydrochloric acid. The reaction mixture freezes below -10 o C and hence lithium chloride was used in sufficient amount to prevent freezing. As the reaction temperature decreases, both the molecular weight of polyaniline and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This result is probably due to the characteristics of the reactional medium and especially to the pKa value (pKa (NDSA) = −0.6). Generally, the elementary analyses results carried out on the polyaniline; prove the presence the oxygen in the formula composition and this attendance due to bound water molecules (25,26). In our product; a substantial degree of hydration is round 0.8 molecule of water per repeat unit.…”
Section: Chemical Composition Of Samplessupporting
confidence: 52%
“…This result is probably due to the characteristics of the reactional medium and especially to the pKa value (pKa (NDSA) = −0.6). Generally, the elementary analyses results carried out on the polyaniline; prove the presence the oxygen in the formula composition and this attendance due to bound water molecules (25,26). In our product; a substantial degree of hydration is round 0.8 molecule of water per repeat unit.…”
Section: Chemical Composition Of Samplessupporting
confidence: 52%
“…Polyaniline was identified on the basis of elemental analysis% (exp./calc. ): C (79.82/78.26), H (5.48/6.52), N (15,06/15,22), IR: 3419 cm −1 , 1448 cm −1 , 1398 cm −1 , 1261 cm −1 , 1091 cm −1 -the bands characteristic for the polymer chain [34,35], UV-vis: band ( max = 286 nm) corresponding to → * transition (there was no n → * band observed and it means that totally reduced form of polyaniline was obtained [34]), and 1 H NMR: characteristic for polyaniline multiplet in the range of 6.5-7.5 ppm, being consistent with the literature data [36,37]. Analysis of the liquid phase was performed by the use of gas and liquid chromatography (GC-FID, GC-MS and HPLC).…”
Section: Carbonylation Procedures and Analysis Of The Productsmentioning
confidence: 99%
“…It was found that high molecular weight and crystallinity of PANi were due to the low polymerization temperature used during the synthesis process [103]. However, it was also reported by Yilmaz et al ( 2009) that the polymerization temperature has no significant effect on the conductivity of PANi [103]. However, contradictory findings were reported by the other researchers that demonstrated that the conductivity of PANi increased with the decreased polymerization temperature [104,105].…”
Section: Polymerization Temperaturementioning
confidence: 96%
“…There have been several studies that reported the influences of polymerization temperature on the molecular weight and conductivity of PANi [99][100][101][102]. It was found that high molecular weight and crystallinity of PANi were due to the low polymerization temperature used during the synthesis process [103]. However, it was also reported by Yilmaz et al ( 2009) that the polymerization temperature has no significant effect on the conductivity of PANi [103].…”
Section: Polymerization Temperaturementioning
confidence: 98%